Evaluation of oral administration of chestnut tannins in preventing calf diarrhoea. Issue 1 (1st January 2021) - Bonelli, Francesca; Turini, Luca; Paganelli, Aurora; Conte, Giuseppe; Meucci, Valentina; Sgorbini, Micaela; Buccioni, Arianna; Mele, Marcello
Abstract: We evaluated the preventive effects of the oral administration of chestnut tannins ( Castanea sativa ) together with its potential metabolic effect on calf diarrhoea. Forty Italian Friesian female calves were included and divided into Group C (control group) and Group T (tannin-treated group). From the third day of life (T0) for the following 56 days (T56), calves from Group C received 2 L of warm water, while 10 g of chestnut tannin powder extract were added to Group T. Calves were weighed at birth and at T56. Daily faecal score evaluation was performed according to the literature. The age at diarrhoea onset (TDE) and the duration of the diarrhoeic episode were recorded. Blood methaemoglobin and liver enzymes were evaluated weekly starting from T0 to T56 by spectrophotometer and clinical chemistry analysis, respectively. The t-Student and chi-square tests were performed. The TDE was higher ( p = .04) in Group T than in Group C (12.0 ± 8.2 and 7.7 ± 3.8 days, respectively). There were no differences for ADG between the groups. Group C spent 24.4% of the whole period with diarrhoea, whereas Group T experienced diarrhoea for 18.9% of the period ( p = .001). All the blood and serum analytes were within physiological values. The administration of tannins in calves from the third day of life seemed to delay the onset of diarrhoea by almost four days, suggesting effective preventive action of chestnut tannins. HIGHLIGHTS: The oral administration of chestnut tannins in calves seemed to delay the onset of diarrhoea by almost four days, thus showing a preventive effect. The oral administration of chestnut tannins may lead to a better and shorter recovery of the calf, thus decreasing the use of antibiotics.